2015
DOI: 10.5222/iksst.2015.063
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the poisoning cases administered in intensive care unit

Abstract: Araştırma ÖZETAmaç: Çalışmamızda, 2010-2014 Material and Methods: We retrospectively reviewed the records of all the patients above 10 years age treated in Elazığ Research and Training Hospital Intensive Care Unit with the diagnosis of poisoning between January 2010 and January 2014.Results: A total of 480 patients (women, n=334; 69.6%, mean age, 26.2±12.01 yrs and men, n=146; 30.4%, mean age, 28.3±11.8 years) were included in the study. The most common cause of poisoning was related to drug therapy (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…While 59.5% (n=100) of drug intoxications were female, 92.3% (n=24) of drug abuse cases were male. The mean age and distribution range of drug intoxications was 27.8±8.3 (17-67) years, while the mean age and distri-bution range of drug users was 26.5±3.8 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) years. While the mean duration of stay in the ICU was 2.3±1.2 days for drug intoxications, it was 2.8±1.9 days for drug use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While 59.5% (n=100) of drug intoxications were female, 92.3% (n=24) of drug abuse cases were male. The mean age and distribution range of drug intoxications was 27.8±8.3 (17-67) years, while the mean age and distri-bution range of drug users was 26.5±3.8 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) years. While the mean duration of stay in the ICU was 2.3±1.2 days for drug intoxications, it was 2.8±1.9 days for drug use.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that pre-existing psychiatric problems are an essential factor in suicidal intoxication attempts. Dogan et al 10 in 23% of the patients, Yeşiller et al 17 in 34.1% of patients, and Urfalıoğlu et al 18 emphasized that 51% of the patients had a history of psychiatric illness. In our study, 35.1% of intoxication cases had a history of psychiatric illness, which was consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In different studies, intoxication mortality rates range between 0.2% and 23.5% [7] [14] [16] [24]. Kose et al showed that 29.4% of the patients needed mechanical ventilation support and the mortality rater in their findings was 23.5% [25].…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmamızda yoğun bakım ünitemize kabul edilen hastaların intihar amacıyla en çok ilaç kullandıkları tespit edilmiş olup bu oran %70,5 olarak bulunmuştur. Kullanılan ilaçlar incelendiğinde ilk sırada analjezikler, ikinci sırada ise antidepresanlar gelmekte ve bu sonuçlar literatürle uyum göstermektedir (9,(13)(14)(15). İntihar amacıyla bu ilaçların tercih edilme sebeplerin başında ilaçlara reçetesiz olarak çok kolay ulaşılması ve yaygın olarak kullanılması olduğunu düşünüyoruz.…”
Section: Discussionunclassified